Tata Kelola Kedaulatan Laut Indonesia Sebagai Negara Maritim - AMALIYA, NADHIFAH (Maliki Interdisciplinary Journal, 2025)
As a land and sea dweller, farmer and sailor, Indonesia is a self-aware nation. The founding fathers of the nation truly realized that the water, straits, and oceans between the tens of thousands of Indonesian islands—from Rondo Island to Merauke, from Miangas Island to Deli Island, from Sekatung Island to Ndana Island—are a unified whole. As the largest archipelagic country in the world with international recognition without military power, Indonesia is the only country capable of expanding its sovereign territory and sovereign rights. The sea plays an important role in strengthening and uniting a country because it is a means for national unity, defense and security, diplomacy, and, most importantly, for the prosperity and welfare of the country and its people because of the abundant potential of marine resources. Indonesia is a maritime country with thousands of islands. Most of this country consists of water, and the rest is land. The geographical aspect of the Unitary State of the Republic of Indonesia becomes more strategically valuable after Indonesia was recognized as an archipelagic country by the international community. In addition to its position at the crossroads of two continents, Asia and Australia, and two oceans, the Pacific Ocean and the Indian Ocean, Indonesia is also located between the Indian Ocean and the South China Sea and the East Asia Sea. After that, the independence and territorial integrity of Indonesia became the basis for designing a complete and comprehensive development plan.